Eco-epidemiological model with fatal disease in the prey. (June 2020) - Greenhalgh, David; Khan, Qamar J.A.; Al-Kharousi, Fatma Ahmed
Abstract: We investigate a model consisting of a predator population and both susceptible and infected prey populations. The predator can feed on either prey species but instead of choosing individuals at random the predator feeds preferentially on the most abundant prey species. More specifically we assume that the likelihood of a predator catching a susceptible prey or an infected prey is proportional to the numbers of these two different types of prey species. This phenomenon, involving changing preference from susceptible to infected prey, is called switching. Mukhopadhyay studied a switching model and proposed that the interaction of predators with infected prey is beneficial for the growth of the predator. In this model, we assume that the predator will eventually die as a result of eating infected prey. We find a threshold parameter R 0 and showed that the disease will be eradicated from the system if R 0 < 1 .